2023
DOI: 10.3390/buildings13030655
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Rheological Properties of Formic Acid Lignin Modified Asphalt

Abstract: Lignin is a major waste product of biofuel and paper industries that can be used as a modifier to improve the relevant properties of asphalt. To investigate the effect of lignin and formic acid lignin wood incorporations into asphalt and the effect on asphalt binder that was unaged and aged for 85 min, 5 h, and 10 h, a series of tests were conducted, including high- and low-temperature rheological tests by a dynamic shear rheometer (DSR), followed by Fourier transform infrared spectroscopy (FTIR) tests, and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, this also led to a decrease in low-temperature performance, as shown by their Bending Beam Rheometer (BBR) test results [20]. Additionally, Cai et al (2023) investigated the effect of lignin and formic acid lignin additives at concentrations of 5 and 10% [21]. Their study revealed that the inclusion of these additives could signifi-Appl.…”
Section: Lignin-modified Bitumenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this also led to a decrease in low-temperature performance, as shown by their Bending Beam Rheometer (BBR) test results [20]. Additionally, Cai et al (2023) investigated the effect of lignin and formic acid lignin additives at concentrations of 5 and 10% [21]. Their study revealed that the inclusion of these additives could signifi-Appl.…”
Section: Lignin-modified Bitumenmentioning
confidence: 99%
“…Sci. 2023, 13, 7766 3 of 25 cantly enhance the properties of the asphalt at high temperatures, while also improving its resistance to fatigue and cracking at low temperatures [21].…”
Section: Lignin-modified Bitumenmentioning
confidence: 99%
“…The incorporation of biowaste enables the performance enhancement of asphalt at high and low temperatures, such as lignin waste, corn stover oil, and plant fibers, which have attracted widespread concerns for researchers [1][2][3]. A vast amount of bagasse, a by-product of the sugar industry, is generated annually in the world.…”
Section: Introductionmentioning
confidence: 99%